The influence of illness‐related variables, personal resources and context‐related factors on real‐life functioning of people with schizophrenia. Issue 3 (October 2014) - Galderisi, Silvana; Rossi, Alessandro; Rocca, Paola; Bertolino, Alessandro; Mucci, Armida; Bucci, Paola; Rucci, Paola; Gibertoni, Dino; Aguglia, Eugenio; Amore, Mario; Bellomo, Antonello; Biondi, Massimo; et al.
<x xml:space="preserve">Abstract</x> In people suffering from schizophrenia, major areas of everyday life are impaired, including independent living, productive activities and social relationships. Enhanced understanding of factors that hinder real‐life functioning is vital for treatments to translate into more positive outcomes. The goal of the present study was to identify predictors of real‐life functioning in people with schizophrenia, and to assess their relative contribution. Based on previous literature and clinical experience, several factors were selected and grouped into three categories: illness‐related variables, personal resources and context‐related factors. Some of these variables were never investigated before in relationship with real‐life functioning. In 921 patients with schizophrenia living in the community, we found that variables relevant to the disease, personal resources and social context explain 53.8% of real‐life functioning variance in a structural equation model. Neurocognition exhibited the strongest, though indirect, association with real‐life functioning. Positive symptoms and disorganization, as well as avolition, proved to have significant direct and indirect effects, while depression had no significant association and poor emotional expression was only indirectly and weakly related to real‐life functioning. Availability of a disability pension and access to social and family incentives also showed a significant direct association with functioning. Social cognition, functional capacity, resilience, internalized stigma and engagement with mental health services served as mediators. The observed complex associations among investigated predictors, mediators and real‐life functioning strongly suggest that integrated and personalized programs should be provided as standard treatment to people with schizophrenia.